APPROACHES TO INSTRUCTING ENGLISH WITHIN TECHNICAL UNIVERSITIES - Mansurova Shohista Ismailovna; Umarov Xondamir Alisher o‘g‘li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This paper examines diverse methodologies for imparting English language skills within technical universities. It scrutinizes varied pedagogical techniques utilized to augment English proficiency among students enrolled in technical fields of study. The research endeavors to offer valuable insights into efficacious strategies for English language education customized to the specialized requirements of students within technical university settings.